Analysis of Technical Efficiency of Milkfish Pond Farming in Sedari Village, Cibuaya District, Karawang Regency - Sri Rahayu Utami; Mohamad Sam’un; Yeni Sari Wulandari (Universitas Islam Lamongan, 2024)
Milkfish is one of the leading aquaculture commodities which has high consumption value in Indonesia. The implementation of milkfish pond cultivation in Sedari Village, Cibuaya District is still not optimal because it is constrained by limited fertilizer provided by agricultural kiosks. The aim of this research is to identify the influence of production factors on production and to analyze the level of technical efficiency. The data analysis method used is the Stochastic Frontier production function. The research results show that the production factors that have a real and significant influence are pond area, seeds and labor. Meanwhile, the variables fertilizer, feed, pesticide, water pump and technology dummy did not have a significant effect on milkfish production in Sedari Village. Milkfish farming in Sedari Village is technically efficient because the average technical efficiency value is 0.84 with the highest efficiency level being 0.95 and the lowest efficiency level being 0.10.